1979
DOI: 10.1121/1.383532
|View full text |Cite
|
Sign up to set email alerts
|

Representation of steady-state vowels in the temporal aspects of the discharge patterns of populations of auditory-nerve fibers

Abstract: This paper is concerned with the representation of the spectra of synthesized steady-state vowels in the temporal aspects of the discharges of auditory-nerve fibers. The results are based on a study of the responses of large numbers of single auditory-nerve fibers in anesthetized cats. By presenting the same set of stimuli to all the fibers encountered in each cat, we can directly estimate the population response to those stimuli. Period histograms of the responses of each unit to the vowels were constructed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
239
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(254 citation statements)
references
References 50 publications
13
239
0
Order By: Relevance
“…This was shown by earlier studies to be true for noise [ 10,281, for tones [21] and for vowels [43]. In this report we have also shown that the output of a linear model based on the first-order cross-correlation functions deviates little from the output of fibers which show a large change in their tuning properties when the stimulus intensity is raised from just above threshold to physiological levels (50-70 dB above threshold).…”
Section: Discussionsupporting
confidence: 82%
“…This was shown by earlier studies to be true for noise [ 10,281, for tones [21] and for vowels [43]. In this report we have also shown that the output of a linear model based on the first-order cross-correlation functions deviates little from the output of fibers which show a large change in their tuning properties when the stimulus intensity is raised from just above threshold to physiological levels (50-70 dB above threshold).…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, several physiological studies of the peripheral and central auditory system of animals have used speech-like stimuli to elucidate potential coding strategies of the human auditory system (e.g., Delgutte and Kiang, 1984;Eggermont, 1995;Sachs and Young, 1979;Schreiner, 1998;Steinschneider et al, 1990;Wong and Schreiner, 2003;Young and Sachs, 1979). Studies of general features of human and animal vocalizations, such as fundamental frequency of the sound source (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Phase locking may be particularly important for coding the relative levels of components in complex sounds (23). When the level of a component is increased relative to that of the other components, the degree of phase locking to that component increases.…”
Section: Coding Of Sound Levelmentioning
confidence: 99%
“…2. By the relative amount of phase locking to the different frequency components in neurons with different CFs (23). For example, if a speech sound has a formant with a frequency of 1,400 Hz, neurons with CFs around 1,400 Hz will show phase locking to the formant frequency.…”
Section: Coding In Normal Hearingmentioning
confidence: 99%